Simon Hailwood, How to be a Green Liberal - Turvey, Jacaranda (Journal for the study of religion, nature and culture, 2005)
Simon Hailwood, How to be a Green Liberal (Chesham: Acumen Publishing, 2004), pp. 197. Paperback, £16.99, ISBN 1-9026-8384-6.